Occupational medical and clinical profile in professional drivers of an occupational health center in Lima Metropolitana, 2014 - 2018 - Barreto-Munive, Marcela (2020)
Objetives: To describe the occupational medical characteristics of professional drivers and the toxicological results present in traffic accidents in an occupational health center in Metropolitan Lima. 2014-2018. Material and methods: Retrospective descriptive study of secondary source data analysis. The sample size analyzed was 11520 professional drivers from the city of metropolitan Lima during 2014 to 2018, selected from an unnamed database using a probabilistic simple randomization sample. Univariate descriptive statistics were used using absolute and relative frequency values, calculation of 95% confidence intervals and error diagrams for each of the variables, identifying the differences in each of the categories or levels of the variable. The information processing was performed in the statistical program R version 3.6. Results: 64% of drivers suffer from overweight or obesity, 58% of drivers suffer from some vision illness, 67% were always on the lookout in each driving, 73% of drivers were acts for car driving and a 13.3% of drivers who suffered a traffic accident were under the influence of drugs. Conclusions: Professional drivers treated in occupational health frequently have obesity and presbyopia as a visual defect; while 27% were qualified as fit for their functions, but with restrictions. The drugs most frequently detected in drivers with traffic accidents were alcohol and marijuana.